Effect of salinity and alkalinity on dynamic adsorption of anionic surfactant and oil recovery in alkaline-surfactantpolymer flooding using a sand pack model - Mohd Noor, Nur Sarah; Tengku Mohd, Tengku Amran; Jaafar, Mohd Zaidi (Universiti Teknologi MARA Shah Alam, 2025)
Alkaline-surfactant-polymer (ASP) flooding is a widely used enhanced oil recovery (EOR) method, but it has reliability issues, particularly surfactant adsorption that reduces efficiency. Surfactant adsorption becomes complex in the presence of alkaline and polymer, which exhibit uncertain behaviour at varying salinity and alkalinity. This study investigates the impact of brine and alkaline concentrations on the adsorption of anionic surfactant and the corresponding oil recovery in ASP flooding. The ASP formulation consisted of 2,000 ppm sodium dodecyl sulphate (SDS), 500 ppm partially hydrolysed polyacrylamide (HPAM) and 10,000 to 30,000 ppm sodium carbonate (Na₂CO₃) as the surfactant, polymer and alkaline, respectively. Sodium chloride (NaCl) was prepared at concentration 10,000 to 30,000 ppm to investigate the effect of salinity. Quartz sand (150 to 250 µm) was packed into a sand pack model for dynamic adsorption and oil recovery tests. The critical micelle concentration (CMC) of SDS was determined to be 2,200 ppm using the Du Noüy ring method. Adsorption was measured using a UVVis spectrophotometer. In dynamic adsorption, as salinity increases from 10,000 ppm to 30,000 ppm, surfactant adsorption increases as much as 10% from 0.69 mg/g to 0.76 mg/g. Meanwhile, surfactant adsorption decreases as much as 22% from 0.69 mg/g to 0.54 mg/g with increasing alkalinity from 10,000 to 30,000 ppm, respectively. The highest oil recovery of 75% original oil in place (OOIP) was achieved at 10,000 ppm brine and 30,000 ppm alkaline, which also exhibited the lowest adsorption. In conclusion, alkaline concentration has been the most determining factor, which has significant impact in minimising the surfactant adsorption, while enhancing the oil recovery in ASP flooding.